2015
DOI: 10.1021/acs.jpca.5b03406
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopic Investigation of Photoionization-Induced Acidic C–H Bonds in Cyclic Ethers

Abstract: Infrared (IR) predissociation spectroscopy based on vacuum-ultraviolet photoionization detection is performed for the neutral and cationic tetrahydrofuran (THF) and tetrahydropyran (THP). The CH bonds in neutral THF and THP are regarded as aprotic, even though the CH bonds are weakened by the negative hyperconjugation. After 118 nm photoionization, however, the negative hyperconjugation changes to the positive hyperconjugation and their CH bond acidities remarkably increase. In the IR spectrum of the THF catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Although CH bonds sometimes act as very weak proton donors in the CH···O/N interaction, they are generally regarded as aprotic. , On the contrary, proton transfer from positively charged CH bonds is frequently seen in gas-phase ion–molecule reactions, radiation chemistry, and organic synthesis. However, while the acidities of cationic OH and NH have undergone a great deal of experimental and theoretical investigations, that of cationic CH has attracted much less attention. Recently, barrierless proton transfer from CH has been found in the ionized trimethylamine and dimethyl ether dimers. , These prove that the acidity enhancement of cationic CH and the reaction mechanism has been interpreted by delocalization of the positive charge through the hyperconjugation between the CH and nonbonding orbitals, the electron of which is ejected in the ionization. Infrared (IR) spectroscopic signatures of acidity enhancement have been reported also for the cationic alkanes, which have no nonbonding orbital . This result implies that alkyl groups as well as alkanes can be acidic under the influence of positive charge.…”
mentioning
confidence: 86%
“…Although CH bonds sometimes act as very weak proton donors in the CH···O/N interaction, they are generally regarded as aprotic. , On the contrary, proton transfer from positively charged CH bonds is frequently seen in gas-phase ion–molecule reactions, radiation chemistry, and organic synthesis. However, while the acidities of cationic OH and NH have undergone a great deal of experimental and theoretical investigations, that of cationic CH has attracted much less attention. Recently, barrierless proton transfer from CH has been found in the ionized trimethylamine and dimethyl ether dimers. , These prove that the acidity enhancement of cationic CH and the reaction mechanism has been interpreted by delocalization of the positive charge through the hyperconjugation between the CH and nonbonding orbitals, the electron of which is ejected in the ionization. Infrared (IR) spectroscopic signatures of acidity enhancement have been reported also for the cationic alkanes, which have no nonbonding orbital . This result implies that alkyl groups as well as alkanes can be acidic under the influence of positive charge.…”
mentioning
confidence: 86%
“…43,44 For the hydrated complexes, natural bond orbital (NBO) analysis was also employed with the uB97X-D functional and cc-pVTZ basis set. 48 All relative energies were zero-point energy (ZPE)-corrected in the Gaussian program. 40,41 The optimized structures and NBO diagrams were visualized using the GaussView 5 program.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…Recently, proton transfer processes have been found in many ion–molecule reactions that were explored with infrared vacuum ultraviolet (IR-VUV) spectroscopy. , The energy of a single photon of VUV light (118 nm light) is enough to ionize the great majority of complexes . The development of mass spectrometer technology has enabled us to perform size-selective studies of clusters. Thus, this method not only can directly determine whether proton transfer occurs in the process, but also can help us choose the specific size of cluster we are interested in. , Up until now, it has been reported that IR spectroscopy based on VUV single-photon ionization is used to study the CH bond barrierless proton transfer process in the cationic diethyl ether, tetrahydrofuran, and tetrahydropyran, trimethylamine dimers, and so on. , , Therefore, theoretically, the IR spectroscopy which is based on VUV photoionization detection can be applied to explore the proton transfer reaction of the majority of molecules and clusters . In this study, we also use this method to carry out our experiment.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Up until now, it has been reported that IR spectroscopy based on VUV single-photon ionization is used to study the CH bond barrierless proton transfer process in the cationic diethyl ether, tetrahydrofuran, and tetrahydropyran, trimethylamine dimers, and so on. 11,[21][22][23]31 Therefore, theoretically, the IR spectroscopy which is based on VUV photoionization detection can be applied to explore the proton transfer reaction of the majority of molecules and clusters. 21 In this study, we also use this method to carry out our experiment.…”
Section: Introductionmentioning
confidence: 99%